Treatment of retinal capillary hemangioma using 810 nm infrared laser - Pochop, Pavel; Kodetova, Martina; Dotrelova, Dagmar (Biomedical papers, 2018)
Aim: Presentation of the efficacy of infrared laser for the treatment of retinal capillary hemangioma (RCH). Methods: The treatment and follow-up of nine eyes (fourteen tumors of different sizes and localizations) in seven patients (five children) with RCH. Infrared diode laser (810 nm) was used for modified transpupillary thermotherapy (TTT) in long exposition mode and power between 200 and 1200 mW with a beam diameter of 2 mm (indirect ophthalmoscope, +28 D or +40 D lens) or 0.5 mm-3 mm (slit-lamp) depending on the diameter and localisation of the hemangioma. Results: We achieved complete destruction of the tumor with flat chorioretinal atrophic scar in all cases. Only one tumor regrowth was observed and re-treatment in this case was necessary. Treatment was combined with brachytherapy in a one case. There was one serious complication- total exudative retinal detachment, causing permanent deterioration in visual acuity despite pars plana vitrectomy (PPV). Other complications such as haze and vitreal hemorrhage were transient. The final best corrected visual acuity (BCVA) ranged from 20/20 to counting fingers at 2 feet. Conclusion: Infrared laser can be considered an acceptable therapeutic option for RCH especially for centrally localized lesions. We believe that the role of this therapy will increase in the future.
Keywords: retinal capillary hemangioma; infrared diode laser; transpupillary thermotherapy; treatment; von Hipple-Lindau